Pengaruh Social Media Marketing dan Brand Awareness Terhadap Loyalitas Pelanggan Pada Produk Madame Gie di Binjai - Sebayang, Devi Elsita Br; Lestari, Indawati (Universitas Medan Area, 2024)
The purpose of this study was to determine the effect of social media marketing on loyality consumer, to determine the effect of brand awarness on loyality consumer, to determine the effect of social media marketing and word of mouth onloyality consumer (case study at store Yara Kosmetik Binjai). The population in this study were customers who visited store Yara Kosmetik Binjai with an unknown number of customers, where the number of samples was 191. The data collection technique used in this study was a questionnaire. The analysis technique used in this study ismultiple linear regression, classical assumptions, hypothesis testing and coefficient of determination. The results of this study indicate that social media marketing has a positive and significant effect on loyality consumer, brand awarness has a positive and significant effect on loyality consumer and simultaneously social media marketing and brand awarness have a significant effect on loyality consumer at Toko Yara Kosmetik Binjai.